National Costs Of The Medical Liability System - Mello, Michelle M. (2010)
Concerns about reducing the rate of growth of health expenditures have reignited interest in medical liability reforms and their potential to save money by reducing the practice of defensive medicine. It is not easy to estimate the costs of the medical liability system, however. This article identifies the various components of liability system costs, generates national estimates for each component, and discusses the level of evidence available to support the estimates. Overall annual medical liability system costs, including defensive medicine, are estimated to be $55.6 billion in 2008 dollars, or 2.4 percent of total health care spending.